PENGEMBANGAN E-LKPD BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Anisa Solihati; Fadhilah Rahmawati; Megita Dwi Pamungkas (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to produce a product in the form of E-LKPD based on Realistic Mathematics Education (RME) on linear program materials to improve problem solving mathematical skills that is valid, practical, and effective. The type of research is research and development or R&D (research and development). The development model used is the ADDIE model, namely analysis, design, development, implementation, and evaluation. The subjects of this study were class XI IPA 3 and XI IPA 4 SMAN 2 Grabag, which were divided into experiment classes and control classes. Data collection instruments in the form of questionnaires and pretest-posttest questions. The results of the study obtained were E-LKPD which is very valid with a validity score of 91.7%, very practical with a practicality score of 80.9, and effectiveto improve problem solving mathematical skills with an N-Gain value of 0.61 with a moderate improvement category